Discussing inclusive education: an inquiry into different interpretations and a search for ethical aspects of inclusion using the capabilities approach. Issue 1 (2nd January 2016) - Reindal, Solveig M.
Abstract: Inclusive education emerged as an idea within United Nations Educational, Scientific and Cultural Organization's Special Education Unit and was presented as a new way ahead at the 'World Conference on Special Needs Education' in Salamanca in 1994. Since then, it has been on the global agenda as the overriding political objective within education. In spite of this, the international agreement, on an ideological basis, was not initially founded on a common interpretation of the meaning of 'inclusive education'. However, the Salamanca Statement reflected clearly the idea of overcoming the divide between regular and special education. After 20 years, a vast amount of research and numerous reports and national strategies for implementing inclusive education, there are in these a lack of agreement over a common interpretation of inclusive education. Since 1994, the concept inclusive education has explored the world, so to say, without having landed, and the effort of giving it a clear working definition has thus far been elusive. In order to create a possible common ground for the mutual interpretation of inclusive education, I argue that it is important to see inclusion as an ethical issue. It is crucial to ask again what the purpose of inclusion is. To this end, it is vital to see inclusive education not just as a social and structural matter about how various aspects of a school are organized to meet diverse children's needs in terms of personnel, pedagogical methods, materials and cultural structures, but also to see inclusive education as an ethical issue. Inclusion impinges on ethical questions because it is for the purpose of something. It conveys something that is valuable. Consequently, I find it pertinent to investigate the ethical aspects of inclusion. I do so in this article, firstly, by juxtaposing different interpretations for inclusive education in the literature. Secondly, I suggest some ethical aspects of inclusion in light of the so-called 'capabilities' approach.